Sistema web y agilización administrativa en el Comité de Regantes Nuevo Horizonte – Pueblo Nuevo – Chepén - Cotrina Lezama, Geral Roy (2019)
Nowadays it is impossible to think about the optimization of an administrative system without the use of software, as this would be equivalent to wasting resources, in that sense and witnessing the problem that affects the New Horizon Irrigation Committee, the development was carried out of a custom webbased software tool with the aim of significantly speeding up committee administration. Currently the administrative processes are carried out in a manual and very complex way for the board, the loss of information and confusion in documents, are problems that my person as a user of the same I have experienced them first hand, that is why in the development of This research "web system and administrative streamlining in the New Horizon Irrigation Committee - Pueblo Nuevo - Chepén" will be possible to streamline the main and more complex processes, reducing the time in assistance control, reducing the time in distribution of irrigation orders and increasing the level of user satisfaction towards the system. The present investigation; being due to its orientation of the applied type and the type of preexperimental applied contrast, it was developed in a committee with 4 users, these being its managers, since there are very few of them, the impact on their satisfaction with the implemented system was measured, through the use of surveys, satisfactory results could be corroborated with an improvement of 31.75%. To measure the time in attendance control, a significant sample of 277 attendances from a total of 1120 for each assembly was taken, applying time shots before and after the prototype implementation, which showed a 67.03% reduction in the Time used before When measuring the impact on the delay of the distribution of irrigation orders, a sample of 191 orders of an average per distribution of 416 was taken and with the help of time-takings to contrast the before and after the implementation of the prototype proposed here investigation, a positive impact of 59.58% was achieved in that time. With the results obtained we conclude the profitability of the research, the NPV being greater than 0 and the C/B greater than 1, obtaining 1.19 new sun soles for every 1 new sun that is invested.